Religion and the workplace : pluralism, spirituality, leadership - Hicks, Douglas A. (Cambridge University Press, 2003)
How can company leaders and employees negotiate their different religious and spiritual commitments in the workplace? At a time of international debate over religious conflict and tolerance, workforces in various parts of the world are more diverse than ever before. This book analyzes the situation and proposes constructive solutions.